Physicochemical and Biological Characterization of rhC1INH Expressed in CHO Cells - Ekaterina Zubareva; Maksim Degterev; Alexander Kazarov; Maria Zhiliaeva; Ksenia Ulyanova; Vladimir Simonov; Ivan Lyagoskin; Maksim Smolov; Madina Iskakova; Anna Azarova; Rahim Shukurov (MDPI AG, 2021)
The disfunction or deficiency of the C1 esterase inhibitor (C1INH) is associated with hereditary or acquired angioedema (HAE/AAE), a rare life-threatening condition characterized by swelling in the skin, respiratory and gastrointestinal tracts. The current treatment options may carry the risks of either viral infection (plasma-derived Berinert®) or immune reaction (human recombinant C1INH from rabbit milk, Ruconest®). This study describes the physicochemical and biological characterization of a novel recombinant human C1 esterase inhibitor (rhC1INH) from Chinese hamster ovary (CHO) cells for the treatment of hereditary angioedema compared to the marketed products Berinert® and Ruconest®. The mass spectrometry results of total deglycosylated rhC1INH revealed a protein with a molecular mass of 52,846 Da. Almost full sequence coverage (98.6%) by nanoLC-MS/MS peptide mapping was achieved. The purity and C1s inhibitory activity of rhC1INH from CHO cells are comparable with Ruconest®, although we found differences in charge isoforms distribution, intact mass values, and N-glycans profile. Comparison of the specific activity (IC50 value) of the rhC1INH with human C1 esterase inhibitor from blood serum showed similar inhibitory properties. These data allow us to conclude that the novel rhC1INH molecule could become a potential therapeutic option for patients with HAE/AAE.